The role of playing position in soccer injury characteristics: evidence from sub-elite athletes - Thema, Makete Thomas; Jacobs, Suzanne; van den Berg, Linda; Strauss, Anita; Mahlangu, Mzwandile Prescott (Frontiers in Sports and Active Living, 2025)
This study examines the association between playing position and injury characteristics among sub-elite male soccer players in South Africa. Using a cross-sectional survey, 223 players from four universities were assessed for injury prevalence, type, mechanism, and severity during the 2023 soccer season. Midfielders experienced the highest injury frequency (43.6%), followed by defenders (30.0%), forwards (17.9%), and goalkeepers (8.6%). Lower limb injuries were predominant across all positions (89.6%), with defenders (94.6%) and midfielders (95.1%) at greatest risk, while goalkeepers sustained a significant proportion of upper limb injuries (44.4%) due to their specialized role. Soft tissue injuries were most common among midfielders (78.0%) and defenders (67.6%), whereas goalkeepers reported higher rates of bone-related injuries (66.7%). Defensive actions, such as tackling, accounted for most injuries among defenders (56.8%), while aerial play contributed substantially to goalkeeper injuries. No statistically significant differences in injury severity were found across positions. These findings highlight the influence of playing position on injury characteristics and underscore the need for position-specific injury prevention strategies tailored to sub-elite soccer players.